1990
DOI: 10.1101/gad.4.9.1611
|View full text |Cite
|
Sign up to set email alerts
|

A TATA-like sequence located downstream of the transcription initiation site is required for expression of an RNA polymerase II transcribed gene.

Abstract: TFIID, the TATA-binding protein, was found to stimulate transcription from the adenovirus IVa2 promoter, a promoter considered to lack the TATA motif. Remarkably, a TATA-Iike sequence element located downstream of the transcription start site binds TFIID and is required for TFIID-dependent transcription from the IVa2 promoter. Transcription from the IVa2 and the adjacent adenovirus major late promoter (Ad-MLP) is divergent, and the cap sites are separated by 212 nucleotides. Nevertheless, the TATA motifs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…Transcription from the Ad-IVa2 and ML promoters occurs on different DNA strands (15). Using recombinant yeast TFIID, we demonstrated that transcription of this so called TATAless promoter was dependent on TFIID (16). Upon inspection of IVa2 promoter sequences, a TATA-like sequence (5'-TATAGAAA-3') was discovered -20 nucleotides downstream of the IVa2-transcriptional start site (16).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Transcription from the Ad-IVa2 and ML promoters occurs on different DNA strands (15). Using recombinant yeast TFIID, we demonstrated that transcription of this so called TATAless promoter was dependent on TFIID (16). Upon inspection of IVa2 promoter sequences, a TATA-like sequence (5'-TATAGAAA-3') was discovered -20 nucleotides downstream of the IVa2-transcriptional start site (16).…”
mentioning
confidence: 99%
“…Using recombinant yeast TFIID, we demonstrated that transcription of this so called TATAless promoter was dependent on TFIID (16). Upon inspection of IVa2 promoter sequences, a TATA-like sequence (5'-TATAGAAA-3') was discovered -20 nucleotides downstream of the IVa2-transcriptional start site (16). An initiator motif was identified in the Ad-IVa2 promoter; in contrast to the TATA motifs, the initiator motifs in the IVa2 and ML promoters were oriented in opposite directions.…”
mentioning
confidence: 99%
See 3 more Smart Citations